Die asymptotische Zerlegungen der Verteilungsfunktion von der Summe unabhängiger gitterförmiger Zufallsveränderlichen - Pipiras, V. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Пипирас. Асимптотические разложения для функции распределения суммы независимых решетчатых случайных величинV. Pipiras. Rėtinių nepriklausomų atsitiktinių dydžių sumos pasiskirstymo funkcijos asimptotiniai išdėstymai